(untitled) (Altre Modernità, 2018)
The article analyses the short-story “The Master at St Bartholomew’s Hospital 1914–1916” by Joyce Carol Oates (2007) in the broader context of the Jamesian biofiction, a series of novels and tales featuring Henry James as their protagonist. The addition of the prefix “bio-” to “fiction” points out the hybrid nature of these texts, which are a melange of biography, autobiography, criticism and fiction. Oates’s story not only epitomizes this hybridity, but it also proves to be an exploration of the potentiality of this subgenre to penetrate the mystery surrounding James’s persona and saturate the lacunae in his biography by resorting to what David Lodge defined as “the novelist’s licence”. The short-story is yet another evidence of Oates’s fascination with the unsaid in James’s life and prose, because it revolves around the silence into which he sank at the outbreak of the Great War, when he did not write anything in his pocket diaries for three months. In an attempt to go beyond the limits of the historical record, Oates gives insights into the mind of the author by depicting a Henry James in crisis – nagged by doubts about his artistic legacy – in an atmosphere of uncertainty enhanced by a complex intertextual play. The result is ‘a Henry James’ slightly divergent from the historical one: thus, the tale advocates the inaccessibility of the private life of a real individual. Nonetheless, the acknowledgement of this limit spurs the celebration of fictional imagination.